At Translation's Edge - Durovicova, Natasa (Media Matters Ser., 2019)
Since the 1970s, the field of Translation Studies has entered into dialogue with an array of other disciplines, sustaining a close but contentious relationship with literary translation. At Translation's Edge expands this interdisciplinary dialogue by taking up questions of translation across sub-fields and within disciplines, including film and media studies, comparative literature, history, and education among others. For the contributors to this volume, translation is understood in its most expansive, transdisciplinary sense: translation as exchange, migration, and mobility, including cross-cultural communication and media circulation. Whether exploring the Universal Declaration of Human Rights or silent film intertitles, this volume brings together the work of scholars aiming to address the edges of Translation Studies while engaging with major and minor languages, colonial and post-colonial studies, feminism and disability studies, and theories of globalization and empire.